Identification of a preassembled TRH receptor-G(q/11) protein complex in HEK293 cells - Drastichova, Zdenka; Novotny, Jiri (Cell structure and function, 2012)
Protein-protein interactions define specificity in signal transduction and these interactions are central to transmembrane signaling by G-protein-coupled receptors (GPCRs). It is not quite clear, however, whether GPCRs and the regulatory trimeric G-proteins behave as freely and independently diffusible molecules in the plasma membrane or whether they form some preassociated complexes. Here we used clear-native polyacrylamide gel electrophoresis (CN-PAGE) to investigate the presumed coupling between thyrotropin-releasing hormone (TRH) receptor and its cognate G(q/11) protein in HEK293 cells expressing high levels of these proteins. Under different solubilization conditions, the TRH receptor (TRH-R) was identified to form a putative pentameric complex composed of TRH-R homodimer and G(q/11) protein. The presumed association of TRH-R with G(q/11)α or Gβ proteins in plasma membranes was verified by RNAi experiments. After 10- or 30-min hormone treatment, TRH-R signaling complexes gradually dissociated with a concomitant release of receptor homodimers. These observations support the model in which GPCRs can be coupled to trimeric G-proteins in preassembled signaling complexes, which might be dynamically regulated upon receptor activation. The precoupling of receptors with their cognate G-proteins can contribute to faster G-protein activation and subsequent signal transfer into the cell interior.
Keywords: proteiny vázající GTP - alfa-podjednotky Gq-G11; receptory thyroliberinu; transfekce; GTP-Binding Protein alpha Subunits, Gq-G11; buněčné linie; signální transdukce; Cell Membrane; Cell Line; hormon uvolňující thyreotropin; HEK293 Cells; lidé; Thyrotropin-Releasing Hormone; Signal Transduction; Receptors, Thyrotropin-Releasing Hormone; HEK293 buňky; Humans; Transfection; buněčná membrána